UMPSA students receive RM66,000 Student Entrepreneur Grant from Bank Rakyat - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KUALA LUMPUR, 17 August 2023 – A total of 20 students from the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) have received a business grant of RM66,000 from Bank Rakyat UNIpreneur as support for student entrepreneurs to further develop their businesses for the creation of entrepreneurship modules and programmes.